Arcane Register of Language as a Strategy in Nepali Modernist Poetry - Niroula, Dhundi Raj (Patan Pragya, 2020)
This research paper tries to provide an analysis of the Nepali modernist poetry written from 1960onwards approximately for a decade. Literary critics holding different views have been vocal about this unique kind of poetry. They have variously labled the modernist poetry as esoteric, reactionary, obscure, monochromatic, status-quoist and devoid of communicative rationality. After judging the rationale and critical validity of these observations, this researcher argues that the poetry of this period has aimed to express the complexities of the time. So, a number of times, these poets have used an arcane register of language that contains revolutionary zeal at the level of both form and content. Even though the modernist poets in the west came to adulthood amid political, technological, social and scientific transformations commonly identified with modernization, such phenomena were not experienced by Nepali poets, whom we have labeled as the modernist, at their home country. They just derived consciousness from the West and experiment in Nepali poetry. Nepali modernist poetry poses challenges to the reader as it has highly experimented with syntax, rhythm, graphology and semantics as well. The reason behind the intellectualization of the poetry through arcane register of language was their strategy to conceal revolutionary spirit of their poetry from the intolerant despotic regime.